2007
DOI: 10.1002/mds.21295
|View full text |Cite
|
Sign up to set email alerts
|

Structural white matter abnormalities in patients with idiopathic dystonia

Abstract: We investigated whether structural white matter abnormalities, in the form of disruption of axonal coherence and integrity as measured with diffusion tensor imaging (DTI), constitute an underlying pathological mechanism of idiopathic dystonia (ID), independent of genotype status. We studied seven subjects with ID: all had cervical dystonia as their main symptom (one patient also had spasmodic dysphonia and two patients had concurrent generalized dystonia, both DYT1-negative). We compared DTI MR images of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 15 publications
3
47
3
2
Order By: Relevance
“…Besides, it suggests loss of neurons in the prefrontal cortex, SMA and the corpus callosum (Fabbrini et al, 2008). In contrast to this, Bonilha et al (2007) found an increase in FA in the thalamus, basal ganglia and adjacent white matter and significant decreased FA in the frontal projections in 7 patients suffering mainly from CD. In a later study, the same group found disrupted thalamic-prefrontal pathways in 7 patients with mainly CD compared to controls (Bonilha et al, 2009).…”
Section: Diffusion-tensor Imagingmentioning
confidence: 68%
“…Besides, it suggests loss of neurons in the prefrontal cortex, SMA and the corpus callosum (Fabbrini et al, 2008). In contrast to this, Bonilha et al (2007) found an increase in FA in the thalamus, basal ganglia and adjacent white matter and significant decreased FA in the frontal projections in 7 patients suffering mainly from CD. In a later study, the same group found disrupted thalamic-prefrontal pathways in 7 patients with mainly CD compared to controls (Bonilha et al, 2009).…”
Section: Diffusion-tensor Imagingmentioning
confidence: 68%
“…In CD, DTI abnormalities in the putamen, caudate head, pallidum, prefrontal cortex, SMA, and corpus callosum have been previously demonstrated. [19][20][21][22] In patients with focal hand dystonia, VBM data receive support from the recent finding of DTI abnormalities in the fiber tracts connecting the primary sensorimotor areas with subcortical structures. 23 The reduced connectivity reported in the subcortical white matter of the sensorimotor area in DYT1 mutation carriers 24 further supports the axonal loss in this subcortical white matter region and abnormalities in the neuronal density in the overlying cortex, which may contribute to the development of dystonia.…”
Section: Discussionmentioning
confidence: 85%
“…Diffusivity was enhanced in the prefrontal cortex and decreased in the caudate nucleus and putamen [9]. In contrast, in another ROI study, diffusivity in the pallidum, putamen and caudate nucleus was increased in patients with cervical dystonia [6,10]. …”
Section: Introductionmentioning
confidence: 99%